Computational modelling studies of precious mixed metals sulphides - Masenya, Mamago Adolphina (University of Limpopo, 2016)
The stabilities of PtS to PdS and PdS to PtS were investigated using density functional theory within the generalized gradient approximation. Their structural, electronic and mechanical properties were determined to show their stability and the effect of pressure on different compositions. We found good correlation of calculations with available ex-perimental data. The lattice parameters were observed to fluctuate with increasing con-centration for both systems. Furthermore, heats of formation were calculated to deter-mine the relative structural stability of the systems. They predict that the most stable structure is Pd50S50 P42/mmc and Pt25Pd25S50 P42/mmc being the least stable. Pd12.5Pt37.5S50 P42/m is the most stable and Pd50S50 P42/m being the least stable struc-ture. The Pt37.5Pd12.5S50 P1 was said to be the most stable structure and Pd50S50 P1 be-ing the least stable. The phonon dispersion calculations show that Pt50S50 P42/mmc, Pd50S50 P42/mmc, Pd12.5Pt37.5S50 P42/m and Pt50S50 P1 (derived from P42/mmc) are me-chanically stable, consistent with calculated elastic constants. The Pt25Pd25S50 P42/mmc show soft modes, which are due to vibrations of Pt and Pd atoms in the x - y plane which suggests the instability of the structure, in agreement with C66 being negative, and consistent with heats of formation. The lattice parameters decreased steadily with increasing pressure. An anomaly was observed in Pt50S50 P1 (derived from P42/mmc), where the c lattice parameter was found to increase with increasing pressure. The elec-tronic density of states (DOS) were performed on all compositions. The DOS were sub-jected to pressure and it was generally noted that the band gap increases with increas-ing pressure. It was observed that the smaller the band gap, the more stable the struc-ture. Furthermore, phonon dispersions under pressure show that compounds with the P42/mmc and P1 (from P42/mmc) symmetries display the mixing of lower and upper en-ergy bands at pressures above 30 GPa.
Thesis (MSc. (Physics)) -- University of Limpopo, 2016
Keywords: Computational modelling studies; Mixed metals sulphides; Physics